Rapid response to galcanezumab and predictive factors in chronic migraine patients: A 3‐month observational, longitudinal, cohort, multicenter, Italian real‐life study. (6th December 2021) - Vernieri, Fabrizio; Altamura, Claudia; Brunelli, Nicoletta; Costa, Carmelina Maria; Aurilia, Cinzia; Egeo, Gabriella; Fofi, Luisa; Favoni, Valentina; Lovati, Carlo; Bertuzzo, Davide; d'Onofrio, Florindo; Doretti, Alberto; et al.
Abstract: Background and purpose: A rapid response to preventive therapy is of pivotal importance in severely disabled patients with chronic migraine (CM) and diverse preventive treatment failures. This prospective, observational, multicenter real‐life study aimed at investigating the effectiveness of galcanezumab in the first 3 months of treatment of CM patients at 14 Italian headache centers. Methods: All consecutive adult patients with CM diagnosis with the clinical indication for galcanezumab were considered. We collected patients' baseline characteristics, monthly headache days, monthly painkiller intake, migraine clinical characteristics, and disability scale scores during a 1‐month run‐in period (baseline) and the first 3 months of therapy. Possible predictive factors of treatment were considered. Results: A total of 156 patients (82.4% female, aged 47.3 ± 12.3 years) were enrolled. The 65 (41.7%) patients with a consecutive ≥50% response rate (RR) in the 3 months of therapy presented a lower body mass index ( p = 0.004) and more frequently presented unilateral migraine pain ( p = 0.002) and good response to triptans ( p = 0.003). Persistent conversion from CM to episodic migraine was observed in 55.8% (87/156) of patients. They more frequently presented a good response to triptans ( p = 0.003) and unilateral pain ( p = 0.046). At baseline, 131 of 156 (83.9%) patients presented medication overuse (MO). Of these, 61.8% (81/131) no longer displayed MO consistently during the 3 months. These patients were more frequently responders to triptans ( p = 0.002) and less frequently suffered from gastrointestinal comorbidity ( p = 0.007). Conclusions: Unilateral pain, good response to triptans, and normal weight may be associated with a persistent positive response in the first 3 months of therapy with galcanezumab in CM patients. Abstract : Rapid response to preventive therapy and its possible predictive factors are fundamental in patients with chronic migraine (CM). In our study, galcanezumab reduced monthly headache days by at least 50% from baseline in >50% of our real‐life CM patients after the first month, in about two thirds after 3 months, and in >40% during all 3 months of treatment. More than 60% of subjects discontinued medication overuse (MO) during all 3 months of treatment. Unilateral pain, good response to triptans, normal weight, and MO at baseline appeared to be associated with a positive response.